Simple smart implants: simultaneous monitoring of loosening and temperature in orthopaedics with an embedded ultrasound transducer - Hall,T; Cegla,F; van,Arkel RJ (IEEE Transactions on Biomedical Circuits and Systems, 2021)
Implant failure can have devastating consequences on patient outcomes following joint replacement. Time to diagnosis affects subsequent treatment success, but current diagnostics do not give early warning and lack accuracy. This research proposes an embedded ultrasound system to monitor implant fixation and temperature – a potential indicator of infection. Requiring only two implanted components: a piezoelectric transducer and a coil, pulse-echo responses are elicited via a three-coil inductive link. This passive system avoids the need for batteries, energy harvesters, and microprocessors, resulting in minimal changes to existing implant architecture. Proof-of-concept was demonstrated in vitro for a titanium plate cemented into synthetic bone, using a small embedded coil with 10 mm diameter. Gross loosening – simulated by completely debonding the implant-cement interface – was detectable with 95% confidence at up to 12 mm implantation depth. Temperature was calibrated with root mean square error of 0.19 °C at 5 mm, with measurements accurate to ±1 °C with 95% confidence up to 6 mm implantation depth. These data demonstrate that with only a transducer and coil implanted, it is possible to measure fixation and temperature simultaneously. This simple smart implant approach minimises the need to modify well-established implant designs, and hence could enable mass-market adoption.